2013
DOI: 10.1369/0022155413489311
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Endothelial Differentiation in Pulmonary Lymphangioleiomyomatosis Cells

Abstract: Pulmonary lymphangioleiomyomatosis (LAM) is a rare, low-grade neoplasm affecting almost exclusively women of childbearing age. LAM belongs to the family of perivascular epithelioid cell tumors, characterized by spindle and epithelioid cells with smooth muscle and melanocytic differentiation. LAM cells infiltrate the lungs, producing multiple, bilateral lesions rich in lymphatic channels and forming cysts, leading to respiratory insufficiency. Here we used antibodies against four lymphatic endothelial markers—p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…It has also recently emerged that lung biopsy sections from LAM patients stain positively for deposited vWF [22]. The low levels we have observed in LAM serum may be due to the aggregation of vWF at the cystic regions in the lungs which was confirmed in immunohistochemical analysis of LAM lung tissue, much the same as fibronectin deposition observed in LAM patients.…”
Section: Discussionsupporting
confidence: 81%
“…It has also recently emerged that lung biopsy sections from LAM patients stain positively for deposited vWF [22]. The low levels we have observed in LAM serum may be due to the aggregation of vWF at the cystic regions in the lungs which was confirmed in immunohistochemical analysis of LAM lung tissue, much the same as fibronectin deposition observed in LAM patients.…”
Section: Discussionsupporting
confidence: 81%
“…Previously, Hansen et al reported that LAM cells were immunonegative for D2-40, a monoclonal antibody directed against podoplanin (17). In contrast, others found that the majority of LAM cells were immunopositive for D2-40, but its intensity varied and was weaker than that by LEC (9,14). Therefore, the biological significance of podoplanin expression in LAM cells is unclear and remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR and HER2 are expressed on human LECs associated with skin, while EGFR has been shown to be expressed in the intra‐ and peritumoral lymphatic vessels of oral squamous cell carcinoma and the peritumoral lymphatics of colon cancer . In addition, anti‐EGFR therapy improved lung phenotypes in mice models of lymphangioleiomyomatosis, a destructive cystic lung disease characterized by neoplastic lesions that express LEC markers Prox‐1, LYVE‐1, and podoplanin, and producing lymphangiogenic factors VEGF‐C and VEGF‐D . In vitro, EGF‐treated human LECs exhibit enhanced migration and tube formation, while in vivo, EGF treatment leads to increased lymphatic vessel area and size, albeit to a lesser extent than VEGF‐C treatment .…”
Section: Lymphangiogenesis Mechanisms: Major Target Sitesmentioning
confidence: 99%
“…ERBB, homologous to erythroblastoma viral gene product, v-erbB cancer. 179 In addition, anti-EGFR therapy improved lung phenotypes in mice models of lymphangioleiomyomatosis, 180 a destructive cystic lung disease characterized by neoplastic lesions that express LEC markers Prox-1, LYVE-1, and podoplanin, 181 and producing lymphangiogenic factors VEGF-C and VEGF-D. 182 In vitro, EGF-treated human LECs exhibit enhanced migration and tube formation, while in vivo, EGF treatment leads to increased lymphatic vessel area and size, albeit to a lesser extent than VEGF-C treatment. 176 In a xenograft melanoma mouse model, EGF produced by tumors induces lymphangiogenesis, with knockdown of EGF expression decreasing tumor-associated lymphatic vessel density but not blood vessel density.…”
Section: Compared To That Of Normal Endothelial Cells Tumor-associatmentioning
confidence: 99%